2020
DOI: 10.1051/rmr/200002
|View full text |Cite
|
Sign up to set email alerts
|

Quality comparison between two different types of platelet-rich plasma for knee osteoarthritis

Abstract: Introduction: Knee osteoarthritis (KOA), the most common form of osteoarthritis (OA) is a considerable health concern worldwide. Platelet-rich plasma (PRP) is a common therapeutic option for KOA. Different types of PRPs have varying efficacies. However, a comparative analysis of the qualities of these PRPs is lacking. Methods: Two types of PRPs, including autologous protein solution (APS), and leukocyte-poor PRP (LP-PRP) along with whole blood (WB) and platelet-poor plasma (PPP) were characterized for platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…All PRP systems resulted in a significant proportional enhancement of leukocytes. This observation is consistent with previous findings [31][32][33][34][35][36][37][38]. Commercially available PRP systems result in products with varying leukocyte concentrations that can be categorized into two groups: leukocyte-rich PRP (LR-PRP) and leukocyte-poor PRP (LP-PRP).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…All PRP systems resulted in a significant proportional enhancement of leukocytes. This observation is consistent with previous findings [31][32][33][34][35][36][37][38]. Commercially available PRP systems result in products with varying leukocyte concentrations that can be categorized into two groups: leukocyte-rich PRP (LR-PRP) and leukocyte-poor PRP (LP-PRP).…”
Section: Discussionsupporting
confidence: 92%
“…As PRP is mainly used for its anti-inflammatory properties, this finding appears counterintuitive. Previous studies have observed a concentration of pro-inflammatory cytokines, such as IL-1β, IL-6, and TNF-α, especially in LR-PRP products [ 33 , 34 , 38 40 ]. Increased levels of IL-1β and TNF-α directly contribute to cartilage degradation and enhanced IL-6 production, which then enhances inflammatory responses that cause bone resorption in OA [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 aaPRP also exerts anti-inflammatory effects through the presence of cytokines, such as interleukin receptor antagonist and broad antibacterial effects through proteins such as connective tissue–activating peptide-III. 4 5 It has been used in several clinical studies involving soft and hard tissue injuries, as well as burn wounds. 2 6 7…”
Section: Discussionmentioning
confidence: 99%
“…The dose, properties of PRP, administration period, and methods of obtaining the optimum effects vary between PRP therapies. 10 , 11 , 12 , 13 , 14 Moreover, PRP therapy has not been shown to be effective for severely degenerated KOA. Furthermore, changes in cartilage damage, especially reductions in inflammation of the subchondral bone and continuous cartilage surface, observed upon magnetic resonance imaging (MRI) osteoarthritis knee score (MOAKS), suggest that PRP is effective for cartilaginous tissue.…”
Section: Introductionmentioning
confidence: 99%